Mindfulness, self-compassion, resiliency and wellbeing in higher education: a recipe to increase academic performance. Issue 3 (16th March 2022) - Egan, Helen; O'Hara, Mark; Cook, Amy; Mantzios, Michail
ABSTRACT: Universities are facing a difficult challenge in supporting good mental health whilst striving to enhance academic performance. The present study aimed to specifically investigate the relationship between attitudinal and personality constructs that are associated with wellbeing and to explore their association with student academic outcomes. Two-hundred and six undergraduate students were recruited and were given questionnaires measuring mindfulness, self-compassion, resiliency, procrastination, consideration of future consequences, self-criticism and social comparison. At the end of the academic year, the researchers accessed their academic records and documented their academic performance. Results indicated that there are strong, clear associations between better academic performance and higher resiliency, mindfulness, self-compassion and consideration of future consequences, and negative associations to procrastination. We concluded that there is a clear gain to be had in academic performance through enhancing these elements using appropriate interventions which are user friendly, affordable and can be embedded into existing student learning and support to reinforce adaptive coping and life skills.